Growth Hormone Therapy in a Girl with Turner Syndrome – An Experience from Bangladesh - Nahar, J.; Zabeen, B.; Islam, N.; Azad, K. (Journal of Diabetes and Endocrinology Association of Nepal, 2022)
Turner’s syndrome(TS) is the most common chromosomal disorder affecting female. Genetics show that most of the patients have monosomy 45 XO and the commonest phenotype is short stature. Growth hormone deficiency is uncommon but consensus statements have endorsed GH treatment for short girls with Turner syndrome as it is found to be effective to increase growth. Here, we describe a nine year and eleven month old girl presented with short stature (Ht-124cm - 2.2 SDS). She had epicanthic fold, cutis valgus and there was no sign of puberty. The diagnosis of TS was confirmed by Karyotype which revealed chrosomomal pattern 45X0/46XX. After evaluation, rGH treatment was initiated and the dose was titrated to 9.5 mg/m2 /wk. After 6 months of therapy the height velocity rose to 10.2 cm/ year. Growth hormone treatment was stopped after 2 years and 4 months as parents were not willing to continue the therapy. The final height of the patient was 144 cm (-1.2SD). She developed spontaneous menarche and other features of puberty at the age of 12 years 4 months. In Bangladesh, we do not have much report of TS who achieved growth with GH therapy. Simple and regular measurement of children’s height with chart plotting is necessary to pick up children who have short stature with TS. Girls with TS may be benefited from early diagnosis and initiation of treatment with GH.